Folhetos de cordel entre realidade e ficção cotidiana: um estudo da mídia na construção do personagem Seu Lunga - Fonseca, Maria Gislene Carvalho (2014)
In this work, from the case of Mr. Lunga, a character of the brazilian northeastern culture whose stories circulated orally until they turned into verses of cordel (regional literature illustrated by xylographic printing images), we intend to understand that gender of leaflet, as significant cultural product, like media, with specific language features that act as means of construction and transmission of realities. To understand this phenomenon of meaning production in the cordel media, we used hermeneutics as a method and applied the general theory of interpretation in six chosen leaflets. We worked with a constructivist perspective that grounds the discussion of everyday reality and fiction, concepts that are raised around the essence of the character that is real, but it is also part of the creative activities of poets, how both are interrelated and constitute the understanding that individuals have the real. From the analyzes, we realize that each poet presents the fields of significance of Mr. Lunga in a different way, based on subjectivity, intention and mediations between each of them and the discourses they produce. Each cordelist contributes in his own way of significance for the construction of the imaginary Mr. Lunga. The speech of the cordelists contains a number of elements that aim to legitimize as truth the actions described. In this confrontation, our goal in this work is to understand the construction of the fields of signification, where these discourses are located, the production of meaning around a character who is not in a finite field, but transits through many of them, making the boundaries between reality and fiction dynamic